STAYGREEN‐mediated chlorophyll a catabolism is critical for photosystem stability during heat‐induced leaf senescence in perennial ryegrass. (10th March 2022) - Zhang, Jing; Li, Hui; Huang, Xinru; Xing, Jing; Yao, Jiaming; Yin, Tingchao; Jiang, Jiafu; Wang, Puchang; Xu, Bin
Abstract: Suppression of the chlorophyll a (Chl a) Mg‐dechelatase gene, SGR / NYE1, blocks the degradation of Chl a, resulting in a 'stay‐green' trait. In this study, we investigated the effect of Chl a catabolism on plant heat‐induced leaf senescence in perennial ryegrass ( Lolium perenne L.). Under heat stress, the LpSGR ‐RNAi lines not only lost the stay‐green phenotype but also showed accelerated leaf senescence with increased chloroplast disruption, more loss of photosystem (PS) proteins, lower PSⅡ quantum yields, higher levels of energy dissipation, increased accumulation of reactive oxygen species (ROS) and lower ROS‐scavenging enzyme activities. Transcriptome analysis revealed that the suppression of LpSGR downregulated genes encoding PS proteins and ROS‐scavenging enzymes and upregulated those encoding ROS‐generation enzymes under heat stress. To account for the possible side‐effects resulting from constitutive suppression of LpSGR on plant growth and heat tolerance, we constructed an ethanol‐inducible RNAi vector to suppress LpSGR functions. In the absence of ethanol induction, these lines exhibited the same growth and heat tolerance as the wildtype (WT). Upon ethanol induction, the transgenic lines showed compromised heat tolerance and a postharvest stay‐green phenotype. Taken together, SGR‐mediated Chl a catabolism is required for plant heat tolerance. SUMMARY STATEMENT: Here, we report that blocking SGR‐mediated Chl a degradation leads to severe photo‐damage under heat stress conditions. Repressing LpSGR in an inducible manner can retain the stay‐green trait with no compromised heat tolerance in perennial ryegrass ( Lolium perenne ).